PKM Penguatan Kapasitas Masyarakat dalam Mencegah Hoaks Digital Melalui Pengenalan Teknologi Deepfake dan Deteksi Hoaks Mengunakan data Science diKarang Taruna Kecamatan Kerinci Kanan - Mitrin, Abdullah; Kurniawan, Bambang; Rahman, Rudi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service Program (PKM) aims to enhance digital literacy and equip Karang Taruna administrators with adequate digital literacy, information verification skills, and the ability to utilize data science technology to prevent the spread of hoaxes, particularly those based on deepfake technology. The main problems faced by the partner include the low level of education, limited understanding of digital literacy, and lack of skills in using fake information detection technology. The methods applied consist of designing a data science-based hoax detection system (Verifia.ID), providing supporting infrastructure, conducting digital literacy outreach, training on system usage, and evaluating program effectiveness. The results show an increase in participants’ understanding of deepfake hoaxes, improved skills in information verification, and the ability to independently operate the hoax detection application. Thus, this program not only provides solutions to low digital literacy but also supports the creation of a healthier, more critical, and sustainable information ecosystem in rural communities.